You are on page 1of 7

# Nanyang Technological University

## MH1810 (FE1006) Mathematics 1

Tutorial 1 Solutions
Discussion Questions
1. Express the following complex numbers in the form rei ; with r
p
2
(a) 1 +
3
1+i
(b)
1 i
Solution (a)
q
p 2
p 2
p 2
12 + 3
r = 1 + 3i
= 1 + 3i =
p
p
arg 1 + 3i = tan 1 13 = 3
p 2
p
Thus, arg 1 + 3i = 2 arg 1 + 3i = 23 .
p 2
Therefore 1 + 3i = 4ei2 =3 .
Alternative Solution
p
Note that 1 +
3

0; and

<

=4

p
2
3i = 2 + 2 3, which lies in second quadrant.
q
p
Thus the required modulus is ( 2)2 + (2 (3)3 ) = 4, and
p
2
, where tan 1 3 = 3 .
the principal argument is
3
2

= 1+

(b)
1+i1+i
(1 + i)2
1 + 2i
1+i
=
=
=
1 i
1 i1+i
1+1
2
Alternative Solution
p
p
1 + i = 2e 4 i and 1 i = 2e 4 i .p
2
1+i
j1 + ij
Thus, we have
=
= p = 1, and
1 i
j1 ij
2
1+i
arg(
) = arg(1 + i) arg(1 i) = 4 ( 4 ) = 2 .
1 i
1+i
Therefore,
= i.
1 i

= i = ei

=2

## 2. Suppose that p(x) = a0 + a1 x + ::: + an xn is a polynomial in x with real coe cients ak s.

Show that if a complex number z is a solution of p(x) = 0, then the conjugate z of z is
also a solution of p(x) = 0:
Proof. Recall that z is a solution of p(x) = 0means that p(z) = 0.
Our aim is to prove that p(z) = 0.
We apply the following properties of taking conjugation:
z1 + z2 = z 1 + z 2 ; z1 z 2 = z 1

z 2 ; z k = (z)k

a = a; for a 2 R

p(z) = a0 + a1 z + a2 z 2 + ::: + an z n
+ an z n

= a0 + a1 z + a2 z 2 +
= a0 + a1 z + a2 z 2 +
= a0 + a1 z + a2

z2

+ an z n
+ an

zn

+ an z n

= a0 + a1 z + a2 z 2 +
= p (z)
= 0: (given p (z) = 0)
=0

(z k = z k )
(ak s are real)
(ak z k = ak z k )
(z + w = z + w)

3. If z1 = r1 (cos

+ i sin

1)

and z2 = r2 (cos

r1
z1
=
(cos (
z2
r2

+ i sin

2)

2) ;

+ i sin (

## r1 ; r2 > 0; show that

2 )) :

Proof.

z1
r1 (cos 1 + i sin 1 )
=
z2
r2 (cos 2 + i sin 2 )
r1 (cos 1 + i sin 1 ) cos 2 i sin 2
=
r2 (cos 2 + i sin 2 ) cos 2 i sin 2
r1 (cos 1 cos 2 + sin 1 sin 2 ) + i (sin 1 cos
=
r2
cos2 2 + sin2 2
r1
=
(cos ( 1
2 ) + i sin ( 1
2 )) (Proved)
r2

sin

2 cos 1 )

cos2 + sin2 = 1
cos

1 cos 2

+ sin

1 sin 2

= cos (

2)

sin

1 cos 2

sin

2 cos 1

= sin (

2)

## 4. Use De Moivres Theorem to express the trigonometric functions in terms of cos

sin :

and

(a) cos 4
(b) sin 4
Solution By De Moivres Theorem, we have cos 4 + i sin 4 = (cos + i sin )4 .
We can obtain an expression of cos and sin by comparing the real parts and the
imaginary parts of the two complex numbers.
cos 4 + i sin 4 = (cos + i sin )4
= cos4 + 4 cos3 (i sin ) + 6 cos2 (i sin )2 + 4 cos (i sin )3 + (i sin )4
= cos4

4 cos sin3

cos 4 = cos4

4 cos sin3

5. Suppose

## 6= 2m where m 2 Z. Prove that

n
sin n + 12
1 X
+
cos k =
2
2 sin 2
k=1

Proof. Note that cos k is the real part of (cos k + i sin k ) = (cos + i sin )k , for
k = 1; 2; 3 : : : ; n. This suggests that we look at the real part of
(cos + i sin ) + (cos 2 + i sin 2 ) +

+ (cos n + i sin n )

ei

(1):

zk

eik

## Let z = cos + i sin =

. By De Moivres Theorem, we have
=
, where k =
2
3
n
1; 2; 3; : : : ; n. Then the above expression (1) is z + z + z +
+ z . We shall look
at the geometric sum 1 + z + z 2 + z 3 +
+ z n . Recall the geometric sum formula
1 z n+1
1 + z + z2 +
+ zn =
.
1 z
n
X
1 + z + z2 + z3 +
+ zn =
(cos k + i sin k )
=

k=0
n
X

(cos + i sin )k =

k=0

=
=

ei(n+1=2)
e i =2 ei =2
cos
2 + i sin

z n+1
1 z

( )

i =2

cos

n+

1
2

+ i sin

n+

1
2

2i sin 2
sin

n+

1
2

+ sin 2

2 sin 2

## Comparing the real parts,

n
X
sin
cos k =

n+

1
2

+ sin 2

2 sin 2

k=0

Thus

zk =

k=0

ei(n+1)
=
1 ei
e i =2 1 ei(n+1)
=
e i =2 (1 ei )
1

n
X

+i

cos 2

sin

cos

n+

1
2

2 sin 2
n+

1
2

2 sin 2

1
+ :
2

sin n + 12
1 X
+
cos k =
2
2 sin 2
k=1

Remarks
(*) The denominator of the expression on the right is 2 sin 2 which is obtainable from
e i =2 ei =2 = 2i sin 2 . Thus we multiply both numerator and denominator by
e i =2 .
Comparing the imaginary parts, we have
n
X
cos 2 cos n + 12
sin k =
:
2 sin 2
k=1
4

8i. Then z 3 =

## Solution Let z be a cube root of

arg ( 8i) = 2 . Therefore

z 3 = 8e

i =2

8i = 8e

i =2

= 23 ei(

=2+2k )

; k 2 Z:

It follows that
z = 2ei(

=2+2k )=3

5
= 2 cos
6
p
p
=
3 i; 3

; k=

1; 0; 1

+ i sin

5
6

h
; 2 cos

i; 2i

+ i sin

h
; 2 cos

+ i sin

## Hence, if z 3 = 8i; then ( z)3 =p

( 1)3 z 3 p
= 8i. Therefore, each ( z) is a cube root of 8i,
i.e., distinct cube roots of 8i are 3 + i;
3 + i; 2i.
7. Solve the following equations.
(a) z 4 + 4z 2 + 16 = 0
(b) z 4 + 1 = 0
(c) z 3 + z 2 + z + 1 = 0,
Solution Recall that:

az 2

b2
2a

+ bz + c = 0 ) z =

4ac

## (a) z 4 + 4z 2 + 16 = 0 () w2 + 4(w) + 16 = 0, which is a a quadratic equation in

w = z2.
Using the formula for quadratic root, we obtain
p
p
4
42 4 (16)
2
w=z =
= 2 2 3i = 4ei(2 =3+2k ) or 4ei( 2 =3+2k )
2
Therefore, we have
z = 2ei(
= 2e
=

=3+k );
i2 =3

k=
i =3

1; 0 or 2ei(
i =3

; 2e
; 2e
p
p
i 3; 1 + i 3; 1

=3+k )

; k = 0; 1

i2 =3

; 2e
p
p
i 3; 1 + i 3

(b)
z4 =

1=e

## z = ei( +2k )=4 ; k = 0; 1; 2; 3

p
p
p
1 1
1 1
= 2
+ i ; 2
+ i ; 2
2 2
2 2

1
2

p
1
i ;
2
2

1 1
+ i
2 2

(c)
[Solution 1] Note that
z4
z

1
= z 3 + z 2 + z + 1 = 0:
1

Therefore
z4

1 = 0; z 6= 1:

Thus
z = ei2k
=

=4

; k = 0; 1; 2; 3; and z 6= 1

1; i; i:

## [Solution 2] Note that z 3 + z 2 + z + 1 = z 2 (z + 1) + (z + 1) = (z 2 + 1)(z + 1).

Thus z 3 + z 2 + z + 1 = 0 () z 2 + 1 = 0 or z + 1 = 0.
Solving z 2 + 1 = 0 gives z 2 = 1 = ei so that z = ei =2 = i or z = ei( +2
ei(3 =2) = i.
Therefore, we have z = i; i; 1.
z 4i 3
2i

## 8. Find the cube roots of i: Hence, solve the equation

the equation in an Argand diagram.
Solution jij = 1; arg (i) =
cube roots of i are ei ; =

5
2 ; 6 or 6 :

4i
2i

2:

)=2

=2+2k ) ; k

1; 0; 1: I.e.,

= ei(

=2+2k )

; k=

1; 0; 1

Therefore
z

4i
2i

## = ei( 2 +2k )=3 ; k =

= ei ; =

2 6

or

1; 0; 1
5
6

5
; or
2 6
6
p
= 2 + 4i; 1 + 4 + 3 i; 1 + 4

z = 4i + 2iei ; =

3 i

Challenging Problems
1. FConsider a regular n-sided polygon circumscribed by the unit circle. Prove that the
product of the length of line segments formed by joining one vertex of the regular polygon
to the rest of the vertices equals to n: (Hint: Consider the nth roots of 1):

and sin4

## in terms of cos k and sin k , where

1
i sin n . Apply De
k = 1; 2; 3. (Hint: Consider z n = cos n + i sin n and n = cos n
z
Moivres Theorem and Binomial expansion.)
Solution
Note that z n +

1
zn

1
2

cos n =

zn +

1
zn

## In particular, we have cos = 12 (z + z1 ).

Thus we have
1
1
(z + )
2
z

cos4 = (cos )4 =
=

1
1
1
1
z 4 + 4(z 3 )( ) + 6(z 2 )( )2 + 4(z)( )3 + ( )4
z
z
z
z

1
24

1
24

1
zn

(z 4 +

1
1
) + 4(z 2 + 2 ) + 6
4
z
z

1
(2 cos 4 + 4(2 cos 2 ) + 6)
24
1
= 3 (cos 4 + 4 cos 2 + 3)
2

Similarly we have z n

sin n =

1
2i

zn

1
zn

## For sin4 , we have

4

sin
=

1
(2i)4

= (sin ) =

1
(z
2i

1
1
4(z 3 )( ) + 6(z 2 )( )2
z
z

z4
=

1
24
=

(z 4 +

1
)
z4

1
(2 cos 4
24
1
= 3 (cos 4
2

4(z 2 +

1
)
z

1
1
4(z)( )3 + ( )4
z
z
1
)+6
z2

4(2 cos 2 ) + 6)
4 cos 2 + 3)